2022
DOI: 10.3389/fpsyg.2022.801263
|View full text |Cite
|
Sign up to set email alerts
|

Music Perception Abilities and Ambiguous Word Learning: Is There Cross-Domain Transfer in Nonmusicians?

Abstract: Perception of music and speech is based on similar auditory skills, and it is often suggested that those with enhanced music perception skills may perceive and learn novel words more easily. The current study tested whether music perception abilities are associated with novel word learning in an ambiguous learning scenario. Using a cross-situational word learning (CSWL) task, nonmusician adults were exposed to word-object pairings between eight novel words and visual referents. Novel words were either non-mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 142 publications
7
10
0
Order By: Relevance
“…In addition to tonal language learners, those who have experience with pitch via musical training have shown better tone discrimination [ 78 ], though not lexical tone learning [ 77 ]. However, in a recent study using the exact same CSWL paradigm and stimuli as in the present study [ 54 ] together with two standard music perception tests, we found that learners with high music perception abilities struggled most with IDS-produced words that had the highest pitch variability, i.e., vMPs. The tonal language speakers tested here struggled across all pair types, which may be due to them consistently using pitch information to discriminate between the exemplars of each word and across words for all pair types.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…In addition to tonal language learners, those who have experience with pitch via musical training have shown better tone discrimination [ 78 ], though not lexical tone learning [ 77 ]. However, in a recent study using the exact same CSWL paradigm and stimuli as in the present study [ 54 ] together with two standard music perception tests, we found that learners with high music perception abilities struggled most with IDS-produced words that had the highest pitch variability, i.e., vMPs. The tonal language speakers tested here struggled across all pair types, which may be due to them consistently using pitch information to discriminate between the exemplars of each word and across words for all pair types.…”
Section: Discussionsupporting
confidence: 43%
“…To confirm whether the additional pitch fluctuations induced by IDS indeed lead to a SUBSET problem and block CSWL in L1 Mandarin L2 English speakers, future research can use words produced in adult-directed-speech (ADS) with minimal pitch variation within and between exemplars of each word to examine whether word learning accuracy improves [ 54 ]. As vMPs naturally contain pitch variability, we expect the SUBSET problem to remain when tested with stimuli produced in ADS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If music training accelerates phonological awareness in children, this association can lead to earlier and proficient reading comprehension in children with music training. Perhaps music training helps children to become efficient readers who can focus better and concentrate for longer periods of time, which ultimately leads to better reading comprehension (Portowitz et al, 2009;Smit et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian approach has been used in many recent papers to handle complex data sets (e.g., Smit et al, 2019Smit et al, , 2022Escudero et al, 2020Escudero et al, , 2022aMilne and Herff, 2020).…”
Section: Bayesian Regression Modelingmentioning
confidence: 99%